INNOVATIVE METHODS FOR ENHANCING THE EFFECTIVENESS OF PRACTICAL GRAMMAR LESSONS IN PHILOLOGY. - Cho’lliyeva Malika Xolmurodovna (KONFERENSIYALAR, 2025)
Abstract. University-level philology students often perceive traditional grammar instruction as tedious, prompting a need for innovative teaching approaches 21 This theoretical article explores how methods such as gamification, blended learning, mobile-assisted learning, AI-based grammar tools, flipped classrooms, and digital collaboration platforms can reinvigorate practical English grammar lessons for philology undergraduates. Grounded in constructivist and communicative pedagogies, Bloom’s taxonomy, and principles of learner autonomy, we discuss each innovative approach’s conceptual underpinnings and potential impact. We argue that these methods create more engaging, student- centered learning environments that foster deeper understanding and practical use of grammar, in contrast to traditional rote learning. Personal reflections address the real-world practicality, challenges, and effectiveness of implementing these innovations in academic contexts.